2016
DOI: 10.1002/jcsm.12101
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatments for fatigue associated with palliative care: executive summary of a Cochrane Collaboration systematic review

Abstract: BackgroundIn palliative care patients, fatigue can be severely debilitating and is often not counteracted with rest, thereby impacting daily activity and quality of life. Further complicating issues are the multidimensionality, subjective nature and lack of a consensus definition of fatigue. The review aimed to evaluate the efficacy of pharmacological treatments for fatigue in palliative care, with a focus on patients at an advanced stage of disease, including patients with cancer and other chronic diseases.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…A Cochrane review and meta-analysis concluded that in the face of limited evidence, it is not possible to recommend a specifi c medication for the treatment of fatigue in palliative care. 40 Another controversial issue is the application of electroconvulsive therapy in palliative care. There are authors who argue that their use should not be completely ruled out and should be considered if it can provide a better quality of life for selected patients.…”
Section: Biological Interventionsmentioning
confidence: 99%
“…A Cochrane review and meta-analysis concluded that in the face of limited evidence, it is not possible to recommend a specifi c medication for the treatment of fatigue in palliative care. 40 Another controversial issue is the application of electroconvulsive therapy in palliative care. There are authors who argue that their use should not be completely ruled out and should be considered if it can provide a better quality of life for selected patients.…”
Section: Biological Interventionsmentioning
confidence: 99%
“…Based on that they showed that there is insufficient evidence to support the use of a specific medicine to treat fatigue in palliative care patients. In this regards, amantadine showed the promised benefit in patients with multiple sclerosis with fatigue and methylphenidate in patients with cancer‐related fatigue …”
Section: Executive Summary Of Cochrane Reviewsmentioning
confidence: 99%
“…The executive summary by Mücke et al was the second Cochrane review that was published in Journal of Cachexia, Sarcopenia and Muscle in March 2016. 7,8 The aim of the Cochrane review was to evaluate the efficacy of pharmacological treatments for fatigue in palliative care, with a focus on patients at an advanced stage of disease, including patients with cancer and other chronic diseases. A total of 1645 publications were selected during the literature search.…”
Section: Executive Summary Of Cochrane Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness and safety of pharmacological and non-pharmacological interventions to alleviate side-effects have been carefully examined. According to a recent Cochrane Review of 45 randomized controlled trials (RCTs) with 4,696 participants, there was insufficient evidence to support the use of prescription medication (such as amantadine, modafinil, and methylphenidate) to treat cancer-related fatigue [8]. In contrast, a systematic review of -2 -11 RCTs showed that complex nursing interventions (including patient education, symptom assessment, counseling and coaching) produced clinically important reductions in chemotherapy-related burden of side-effects by 10-88% [9].…”
Section: Introductionmentioning
confidence: 99%